Effect of tele-nutrition education on weight loss, energy intake, and fat adequacy among obese adults in Banyumas, Central Java, Indonesia - Jati Prasetyo Teguh; Nur Khoiriani Izzati; Aulia Wicaksari Sifa; Ratna Ramadhan Gumintang (BIO Web of Conferences)
Obesity can be caused by imbalanced energy intake and expenditure due to a lack of physical activity. This research aims to analyze the effect of tele-nutrition education on changes in weight loss, energy, and fat adequacy in obese adults. Forty-six obese adults were involved in this study and randomly divided into control and intervention groups. Tele- nutrition education was conducted in the intervention group for 16 meetings. Food consumption data was obtained using the 2x24 hour recall method and anthropometric data using the Omron HBF 375 and Kenko Stadiometer. Statistical tests using SPSS were performed. The results indicated that there was a significant weight loss in the intervention (p=0.008) group, while there was no weight reduction in the control group (p=0.283). The statistical test showed a significant decline in the level of energy adequacy in both the control (-18.2 ± 23.4; p < 0.05) and intervention groups (-25.9 ± 32.0; p<0.05). The intervention group also experienced a significant reduction in fat adequacy (-47.5±82.5; p<0.05) but in the control group, the decrease in fat was not statistically significant (p>0.05). In conclusion, tele-nutrition education had significant benefits on changes in weight loss, levels of energy, and fat adequacy among the intervention group compared to the control group.